Digital Sovereignty and State Power: Indonesia’s Approach to Digital Platforms Regulation - Gumati, Mirna Rahmadina (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
The growing influence of digital platforms has sparked debate over the ideal balance of sovereignty in regulating their operations. While digital sovereignty is essential for safeguarding against external influences, it also risks granting governments extensive control over citizens. Indonesia’s Ministry of Communication and Information (MoCI) Regulation No. 10 of 2021 (MR 10/2021), which governs private-sector Electronic System Organizers, exemplifies this tension. This article examines MR 10/2021’s rationale and impact on Indonesia’s digital society through thematic analysis of YouTube content and discussions with MoCI representatives. The findings reveal that the platform registration mandate reflects a state-centric view of digital sovereignty, emphasizing territorial authority and control. However, a disconnect emerges between the regulation’s stated objectives—such as promoting fair competition, protecting users, and mapping digital industry players—and its implementation. By equating digital platforms with traditional businesses, the regulation facilitates governmental access to electronic data and systems for monitoring, content removal, and law enforcement. To achieve its goals more effectively, the study advocates refining MR 10/2021 and introducing sector-specific policies tailored to the unique dynamics of digital platforms.